2018
DOI: 10.4274/atfm.41736
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Traditional Methods Used by Mothers to Wean Their Infants from Breast- Feeding

Abstract: Objectives: This research was carried out to determine the traditional methods used by mothers to wean infants from breastfeeding. Materials and Methods: Descriptive type of planned study was conducted on mothers who referred to the pediatric polyclinic of a training and research hospital in the province of Ordu between 25 July and 25 August 2017. The universe of research mothers with children between 2-5 years of age (n=362) who applied to the pediatric outpatient clinic, the sample consisted of the mothers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 4 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The study data were collected with a questionnaire developed by the researchers in line with the literature (Hunegnaw et al 2017;Yüzer-Alsaç et al 2018;Dinç et al 2015;Gök-Uğur et al 2018). Inclusion criteria of the study were having a baby between 6 and 36 months and terminated breastfeeding, above 18 years old, literate women.…”
Section: Methodsmentioning
confidence: 99%
“…The study data were collected with a questionnaire developed by the researchers in line with the literature (Hunegnaw et al 2017;Yüzer-Alsaç et al 2018;Dinç et al 2015;Gök-Uğur et al 2018). Inclusion criteria of the study were having a baby between 6 and 36 months and terminated breastfeeding, above 18 years old, literate women.…”
Section: Methodsmentioning
confidence: 99%
“…In traditional communities in New Guinea, it has been reported that weaning by smearing mud on the nipple is common (21). Many studies in Turkey have also reported that repulsive substances are used as a traditional method to wean the child (9,10,24). Considering that the traditional methods applied in the world and Turkey are similar to our research findings, it has been observed that mothers use traditional methods to separate their babies from breast milk and receive information about these processes from their close relatives.…”
Section: Many International and National Organizations Have Accepted mentioning
confidence: 99%
“…The abrupt weaning method, commonly used for weaning, is not recommended except for medical reasons (18). Traditional methods that involve changing the taste of the breast sucked by the baby with pleasure, or the sudden separation of the baby from the mother, can create adverse psychological effects on the child by undermining the bond of trust between mother and baby (10). In this process, the mother should take more care of her baby, hug the baby more, and not be separated from the child so that the baby does not experience breast separation and mother's separation at the same time (10,18,25).…”
Section: Many International and National Organizations Have Accepted mentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding not only means feeding a child, but also has numerous psychological effects such as calming the child down when he/she is afraid, crying or in pain. For this reason, gradual weaning is a crucial process that affects the relationship between breastfeeding and the infant (7,9,11). Weaning practices can vary based on time and culture (12,13).…”
Section: Introductionmentioning
confidence: 99%